Mempertahankan Keberlakuan Pidana Mati Sebagai Jalan Tengah Pro dan Kontra - Widiartana, Gregorius; Chandavasti, Emilia Prasetya (DAS Institute, 2025)
The death penalty remains a subject of debate in various countries, including Indonesia. This debate arises from differing perspectives between those who support it for its deterrent effect and justice for victims and those who oppose it based on human rights concerns and the potential for judicial errors. This study aims to analyze the validity of the death penalty in Indonesia as a middle ground in addressing the ongoing debate. The research employs a normative legal method with a statutory and conceptual approach, focusing on the study of Indonesian criminal law regulations and philosophical perspectives on capital punishment. The findings indicate that the implementation of the death penalty in Indonesia remains relevant, considering aspects of justice, legal certainty, and public interest. However, to bridge differing views, a more selective mechanism should be applied, such as alternative sentencing with probation periods or strict clemency provisions. This analysis asserts that maintaining the validity of the death penalty with stricter regulations can serve as a middle ground accommodating various interests. Therefore, policy reforms regarding the death penalty should be continuously reviewed to ensure its implementation aligns with legal principles and human rights.